Bulk density and relationship air/water of horticultural substrate - Fernandes, Carolina [UNESP]; Corá, José Eduardo [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2004)
Alterações na densidade do substrato durante o cultivo das plantas modificam suas propriedades físicas. O trabalho teve como objetivos caracterizar fisicamente dois substratos hortícolas e avaliar o efeito da densidade na relação ar/água dos mesmos, elaborando funções matemáticas que permitam estimar tal relação a partir da densidade do substrato. Para tanto, determinou-se a distribuição do tamanho das partículas, a densidade e a curva de retenção de água. Procedeu-se o acondicionamento dos substratos em três valores de densidade: 10 (D1), 20 (D2) e 30% (D3) maior que a densidade (D) determinada na fase de caracterização. Partindo das amostras com diferentes densidades, determinou-se a curva de retenção de água dos substratos. A influência do aumento da densidade do substrato na porosidade total (PT), no espaço de aeração (EA), na água disponível (AD), na água facilmente disponível (AFD), na água tamponante (AT) e na água remanescente (AR) foi avaliada pela análise de regressão linear simples e análise polinomial. A composição granulométrica e a curva de retenção de água foram significativamente diferentes para os dois substratos. O aumento da densidade diminuiu a PT e o EA e aumentou a AT e AR. Os maiores valores de AD e AFD foram observados para D1. Foram obtidas equações de regressão que podem auxiliar na escolha da relação ar/água mais adequada para cada condição.

Change on substrate bulk density during the growing period may negatively affect other substrate physical properties and, consequently, plant growth. The objectives of this research were 1) to characterize physical properties of two horticultural substrates (S1 and S2), 2) to evaluate the effect of different bulk densities values of those substrates on their air/water relationship, and 3) to develop mathematical functions to estimate the air/water relationship by increasing substrates bulk density value. First, the distribution of particles size, the bulk density, and the water release curve of the substrates were determined. Then, substrates were packed with three different bulk density values, i.e. 10% (D1), 20% (D2) and 30% (D3), higher than the bulk density (D) determined in the characterization phase. The water release curves were determined for each bulk density value of both substrates. The effect of increasing substrate bulk density in the total porosity (TP), aeration space (AS), available water (AW), easily available water (EAW), buffering water (BW), and in the remaining water (RW) was evaluated using simple linear regression and polynomial analysis. The particles size distribution and the water release curves were significantly different for the two substrates. Increasing the bulk density value decreased TP and AS, and increased BW and RW. The highest values of AW and EAW were observed for D1. Regression equations obtained can be used to choose the more appropriate air/water relationship for each growing condition.
Densidade e relação ar/água de substratos hortícolas
Keywords: particle size distribution; substrate bulk density; water release curve; Regression equation; composição granulométrica; Densidade; curva de retenção de água; equações de regressão